2-cm versus 4-cm surgical excision margins for primary cutaneous melanoma thicker than 2 mm: long-term follow-up of a multicentre, randomised trial. Issue 10197 (10th August 2019) - Utjés, Deborah; Malmstedt, Jonas; Teras, Jüri; Drzewiecki, Krzysztof; Gullestad, Hans Petter; Ingvar, Christian; Eriksson, Hanna; Gillgren, Peter
Summary: Background: The optimal surgical excision margins are uncertain for patients with thick (>2 mm) localised cutaneous melanomas. In our previous report of this multicentre, randomised controlled trial, with a median follow-up of 6·7 years, we showed that a narrow excision margin (2 cm vs 4 cm) did not affect melanoma-specific nor overall survival. Here, we present extended follow-up of this cohort. Methods: In this open-label, multicentre randomised controlled trial, we recruited patients from 53 hospitals in Sweden, Denmark, Estonia, and Norway. We enrolled clinically staged patients aged 75 years or younger diagnosed with localised cutaneous melanoma thicker than 2 mm, and with primary site on the trunk or upper or lower extremities. Patients were randomly allocated (1:1) to treatment either with a 2-cm or a 4-cm excision margin. A physician enrolled the patients after histological confirmation of a cutaneous melanoma thicker than 2 mm. Some patients were enrolled by a physician acting as responsible for clinical care and as a trial investigator (follow-up, data collection, and manuscript writing). In other cases physicians not involved in running the trial enrolled patients. Randomisation was done by telephone call to a randomisation office, by sealed envelope, or by computer generated lists using permuted blocks. Patients were stratified according to geographical region. No part of the trial was masked. The primary outcome in this extended follow-up study was overall survival and the co-primary outcome was melanoma-specific survival. All analyses were done on an intention-to-treat basis. The study is registered withClinicalTrials.gov, numberNCT03638492 . Findings: Between Jan 22, 1992, and May 19, 2004, 936 clinically staged patients were recruited and randomly assigned to a 4-cm excision margin (n=465) or a 2-cm excision margin (n=471). At a median overall follow-up of 19·6 years (235 months, IQR 200–260), 621 deaths were reported—304 (49%) in the 2-cm group and 317 (51%) in the 4-cm group (unadjusted HR 0·98, 95% CI 0·83–1·14; p=0·75). 397 deaths were attributed to cutaneous melanoma—192 (48%) in the 2-cm excision margin group and 205 (52%) in the 4-cm excision margin group (unadjusted HR 0·95, 95% CI 0·78–1·16, p=0·61). Interpretation: A 2-cm excision margin was safe for patients with thick (>2 mm) localised cutaneous melanoma at a follow-up of median 19·6 years. These findings support the use of 2-cm excision margins in current clinical practice. Funding: The Swedish Cancer Society, Stockholm Cancer Society, the Swedish Society for Medical Research, Radiumhemmet Research funds, Stockholm County Council, Wallström funds.